Analysis of User Complaints for Telecommunication Brands on X (Twitter) using IndoBERT and Deep Learning - Hakim, Valianda Farradillah; Riana, Dwiza (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2024)
Tweeting on different official accounts is what users of Twitter (X) do most frequently. These tweets ranging from compliments to critiques. One of the official accounts that gets a lot of tweets from its customers is Telkomsel, an Indonesian telecom company. This study aims to find the maximum accuracy that can be obtained by combining CNN and Bi-LSTM algorithms with IndoBERT embeddings. A considerable accuracy level above 90% is demonstrated by the study, with CNN obtaining the greatest accuracy of 99% at a learning rate of 6*10^-5, along with scores of 98%, 97%, and 97% for precision, recall, and F1 correspondingly.